The phylogenetic relationship and non‐specific symbiotic habit of mycorrhiza fungi from a terrestrial orchid (Cymbidium). (8th April 2016) - Li, Jie; Wang, Renrui; Wang, Zhina; Kuang, Ping
Abstract : To investigate the specificity of the symbiotic relationship between Cymbidium plants and their mycorrhiza fungi, thirty mycorrhiza fungi were isolated from roots of six terrestrial Cymbidium species. The internal transcribed spacer (ITS) region of nuclear ribosomal DNA (rDNA) were amplified by polymerase chain reaction (PCR) with universal fungal primers ITS1/ITS4. All fungal strains isolated from natural roots of orchids were inoculated into the rhizomes of in vitro Cymbidium goeringii . Phylogenetic analysis indicated fungal isolates of different cluster could be obtained from a special terrestrial Cymbidium species. Observation of light microscope and scanning electron microscope showed that fungi entered the cortical tissue by destroying cell wall of epidermal cells, where they formed hyphal knots in the cortical cells and were digested gradually. A large number of small protuberances were visible on cross sections of the rhizome. There was no strict inter‐species specificity between the isolated mycorrhiza fungi and terrestrial Cymbidium .